Shear Strength Behavior of Tire Shred-Dune Sand Admixtures - Ahmad, Abrar (2025)
A Master of Science thesis in Civil Engineering by Abrar Ahmad entitled, “Shear Strength Behavior of Tire Shred-Dune Sand Admixtures”, submitted in July 2025. Thesis advisor is Dr. Magdi El-Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).